Analisis Dalam Pendukung Keputusan Penerimaan Supervisor Industri Manufacturing dengan Menerapkan Metode EDAS dan Pembobotan ROC - Bernadus Gunawan Sudarsono; A Ahyuna; Triyugo Winarko; Dwi Puspita Anggraeni; Zulfi Azhar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Manufacturing industry supervisor is one of the jobs engaged in processing raw goods into whole or semi-finished goods. Honest and responsible supervisors in the company are needed. Therefore, the company is opening the acceptance of supervisors who have a high responsible spirit. However, in accepting supervisors is not an easy thing because finding people who really have a high leadership spirit and are responsible is not an easy thing, therefore a system is needed that can help the company find a decision. The system is a decision support system and in finding these decisions several criteria are needed including Education, Experience, Leadership Ability, Good Interpersonal and Responsibility. And also in order to get accurate results that deserve to be supervisors can use methods where researchers use EDAS methods and ROC weighting. So in the research conducted by the author obtained the highest ranking found in alternative AD7 on behalf of Bambang with a total value of 1,00000 who was selected to be a supervisor of the manufacturing industry with complete requirements and the highest value.